Kontrol diri untuk meningkatkan regulasi emosi pada individu dewasa - Annisa Firdaus Wirandika (Procedia : Studi Kasus dan Intervensi Psikologi, 2026)
Emotional regulation is an individual’s ability to manage and express emotions adaptively. The inability to manage emotions, or emotional dysregulation, can trigger maladaptive behavior. This case study examines a woman who experienced difficulty regulating her emotions after a separation, as evidenced by a tendency to curse when experiencing negative emotions. This study aimed to determine the effectiveness of self-control interventions in improving emotional regulation and coping strategies. The subject was a woman who had divorced her husband. Assessments were conducted through interviews, observations, graphic tests, and the Difficulties in Emotion Regulation Scale–Short Form (DERS- SF). Behavior modification interventions were administered to improve emotional regulation and coping skills. The results showed that self-control interventions improved emotional regulation, allowing the subject to calm down using more adaptive coping strategies, thereby reducing the frequency of maladaptive behaviors such as swearing.